A educação matemática no Brasil da perspectiva do discurso de pesquisadores - Venturin, Jamur Andre [UNESP] (2015)
This study focuses on Mathematics Education, which begs the question of the following inquiry: What do Mathematics Education researchers have to say about Mathematics Education in Brazil?. The objective is to understand the meaning of Mathematics Education in the different ways that it presents itself to researchers speeches in Brazil, focusing in this field of study and trying to outline a style for it. The research data were obtained by interviewing teachers and researches, who work in Brazil and were referenced in III SIPEM. The Husserlian Phenomenology is the philosophical method used for this investigation. The data analysis consisted of two moments: the Ideographic analysis and the Nomothetic analysis. In the first one, the meaning units were broken up into the speech of each significant individual, established by the interrogation. In the second moment, we gathered the meaning units, looking for convergences; this is the moment when we directed ourselves from the individual notion to a core of more comprehensive ideas, which were referred to as Meaning Cores, explaining what Mathematics Education is now and indicating what it could be in the future. This way, we created the following Meaning Cores: 1) The Scientific Production in Mathematics Education; 2) The understanding of/in Mathematics Education; 3) Mathematics Education and Mathematics; 4) The Practices of a Mathematics Teacher; 5) The Mathematics Teacher Training. These Meaning Cores were interpreted and theorized